The effects of temperature and driving current on the key parameters of commercially available, high-power, white LEDs. (December 2016) - Yurtseven, MB; Mete, S; Onaygil, S
High-power LEDs with high luminous efficacies, compact sizes, long lifetimes and a wide colour range, are rapidly taking the place of conventional light sources in general lighting applications. But these properties of high-power LEDs are dependent on temperature and driving current. In this study, 24 samples of commercially available, high-power, white LEDs were measurement for their electrical, optical and thermal characteristics as well as their efficiency, luminous flux, luminous efficacy, correlated colour temperature and colour rendering index over six temperature steps at three different driving currents. LED manufacturers' catalogues including such information will allow consistency between the design and application stages of an installation. Also, it will make the technical and economic optimization of luminaires using high-power LEDs easier.